Life cycles or longer tenures? a performance and employment duration model for Spanish basketball coaches - Gomez-Haro, S.; Salmeron-Gomez, R. (Coaching: An International Journal of Theory, Research and Practice, 2015)
This study analyses the effect of basketball coaches on performance and the question of life cycles on their tenures. From theoretical perspectives like coach-performance relationship, succession theories, life cycle theory and based on a longitudinal analysis from 1997 to 2012 of a professional Spanish basketball league, we show that the objective established at the season's start and coach quality positively influences team performance, that a mid-season coaching change negatively influences performance, and the existence of longer tenures coaches that improve team performance. The work is especially interested for sport managers, sport coaches in their decisions-taking, but it is useful to general management to understand the consequences of the tenures or dismissals of their key managers on results.